IMMU-40. IMMUNE PROFILING OF MATCHED PRIMARY AND RECURRENT GLIOBLASTOMA TUMORS IDENTIFIED CD64 AS A NEGATIVE PREDICTOR FOR SURVIVAL. (12th November 2021) - Shekarian, Tala; Ritz, Marie-Françoise; Martins, Tomàs; Schmassmann, Philip; Hutter, Gregor
Abstract: BACKGROUND: To target tumor-induced immune evasion mechanisms of glioblastoma for clinical research, we aimed at characterizing the immunological changes in patient-matched treatment-naïve and recurrent GBM samples. MATERIAL AND METHODS: Proteins and total RNA were extracted from 15 patient-matched treatment-naïve (primary) and recurrent GBM fresh frozen tumor samples. The expression of genes involved in brain immune responses were compared using Nanostring panels encompassing Cancer and Neuroinflammation genes. Correlation analysis using log2-transformed patient-matched recurrent/primary expression ratio (log2(P/R)) and clinical outcome data (time to relapse and overall survival (OS)) was conducted. Proteomic was conducted to compare total protein expressions. Moreover, immunostaining was performed on a tissue microarray of matched tumor samples to visualize CD64 + cells, CD47 + tumor cells and microglia in order to assess quantitative transcriptome of these specific cell types using GeoMX technology. Functional assays are designed for deciphering phagocytosis induction by factors produced by primary and recurrent tumors. RESULTS: Genes significantly differentially expressed between primary and recurrent tumors revealed "Antigen presentation" and "Microglia Pathogen Phagocytosis" as the most significant pathways enriched in recurrent tumors. Considering individual genes, a strong negative correlation (R 2 >0.4) between log2(R/P) and time to relapse and OS was found for 2 genes, FCGR1A ( CD64 ) and CD47. We observed that only CD64 expression levels in recurrent samples also negatively correlated with OS. CD64 and CD47 proteins were quantified by proteomic analysis and log2 (R/P) of their levels also negatively correlated with time to relapse. Immunostaining revealed numerous CD64-positive cells in tumor biopsies resembling bushy or amoeboid microglia. CONCLUSION: Upregulation of CD64 and CD47 expressions in recurrent GBM was identified as a negative predictor for time to relapse and OS. This suggests an important role of CD64 and CD47 and related inflammation dysregulation in tumor resistance and regrowth. Interfering with CD64-induced functions may represent a novel therapeutic option for GBM.